Rancangan Sistem Informasi Perawatan Preventif Berbasis Website di Bengkel Mekanik Politeknik Manufaktur Negeri Bangka Belitung - Christianty, Licia; Irwan, Irwan; Swengky, Better; Napitupulu, Robert (Politeknik Negeri Lhokseumawe, 2025)
Machine maintenance plays a crucial role in ensuring the smooth operation of practical activities at the Mechanical Workshop of Politeknik Manufaktur Negeri Bangka Belitung. The current manual maintenance process often causes scheduling delays, recording errors, and difficulties in monitoring machine conditions. This study aims to design and implement a web-based preventive maintenance information system to enhance the efficiency and effectiveness of machine management. The development process applies the Agile method using the Laravel framework and MariaDB as the database management system. The system includes key features such as machine data management, maintenance scheduling, submission and approval workflows, automated email notifications, integration with the Google Calendar API, and maintenance and spare part reporting modules. The system was tested using the black box testing method, which confirmed that all functions operated according to user requirements. Questionnaire results from laboratory staff, lecturers, and students indicated that the system improved scheduling consistency, data recording accuracy, and the effectiveness of notification features in reminding users of maintenance schedules. Approximately 50% of respondents agreed that the system successfully manages maintenance scheduling in a structured and computerized manner, while the notification feature helps reduce the risk of maintenance negligence. Therefore, the developed system serves as an effective digital solution to support preventive maintenance management in vocational education environments